Subhalo destruction in the Apostle and Auriga simulations. Issue 4 (17th December 2019) - Richings, Jack; Frenk, Carlos; Jenkins, Adrian; Robertson, Andrew; Fattahi, Azadeh; Grand, Robert J J; Navarro, Julio; Pakmor, Rüdiger; Gomez, Facundo A; Marinacci, Federico; Oman, Kyle A
ABSTRACT: N -body simulations make unambiguous predictions for the abundance of substructures within dark matter haloes. However, the inclusion of baryons in the simulations changes the picture because processes associated with the presence of a large galaxy in the halo can destroy subhaloes and substantially alter the mass function and velocity distribution of subhaloes. We compare the effect of galaxy formation on subhalo populations in two state-of-the-art sets of hydrodynamical Λcold dark matter (ΛCDM) simulations of Milky Way mass haloes, Apostle and Auriga . We introduce a new method for tracking the orbits of subhaloes between simulation snapshots that gives accurate results down to a few kiloparsecs from the centre of the halo. Relative to a dark matter-only simulation, the abundance of subhaloes in Apostle is reduced by 50 per cent near the centre and by 10 per cent within r 200 . In Auriga, the corresponding numbers are 80 per cent and 40 per cent. The velocity distributions of subhaloes are also affected by the presence of the galaxy, much more so in Auriga than in Apostle . The differences on subhalo properties in the two simulations can be traced back to the mass of the central galaxies, which in Auriga are typically twice as massive as those in Apostle . We show that some of the results from previous studies are inaccurate due to systematic errors in the modelling of subhalo orbits near the centre of haloes.